Studies on Nutrient Release Pattern of Neem Fortified Cocoa Pod Husk Fertilizer in an Alfisol - Ogunwole, Ogunlade Moses; Adeoye, Gideon Olajire; Ogeh, Joseph Sunday (JOURNAL OF TROPICAL SOILS, 2012)
A laboratory experiment was carried out at Cocoa Research Institute of Nigeria, Ibadan to evaluate the nutrientrelease pattern of neem fortified cocoa pod husk developed for use as organic fertilizer materials. Cocoa Pod Husk(CPH), Neem Leaf (NL), Neem Seed (NS), CPH + NL (90:10), CPH + NL (80:20), CPH + NS (90:10) and CPH +NS (80:20) were separately applied at the rate of 100 kg N ha-1 into 50 g soil placed in plastic cups. There were sixsampling periods (2, 4, 8, 12, 16, and 20 weeks) after treatment application. Soil N (Kjeldahl), P (Bray 1), K (1 NNH4OAc pH 7) and pH (soil:water ratio 1:2) were determined at each sampling period. The result showed that theorganic materials had significant effect in raising the pH of the soils compared to unamended soil. Neem fortifiedCPH significantly (P < 0.05) increased nitrogen release higher than control at 8, 12 and 16 weeks after application.Phosphorus release was significantly higher in soil treated with CPH, NL, NS and neem fortified CPH than thecontrol at 20 weeks after application. CPH and neem fortified CPH enhanced K release better than NL and NSapplied separately across the incubation periods. Neem leaf and seed powder with higher N content than CPH is aprecursor of N- release into the soil shortly after incorporation.[How to Cite: Ogunwole OM, GO Adeoye, O Fagbola and JS Ogeh. 2012. Studies on Nutrient Release Pattern of Neem Fortified Cocoa Pod Husk Fertilizer in an Alfisol. J Trop Soils 17 (2) : 129-134. Doi: 10.5400/jts.2012.17.2.129]Â Â [Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.2.129]